2021
DOI: 10.1002/kjm2.12434
|View full text |Cite
|
Sign up to set email alerts
|

JMJD5 attenuates oxygen–glucose deprivation and reperfusion‐induced injury in cardiomyocytes through regulation of HIF‐1α‐BNIP3

Abstract: Proteins in Jumonji family function as histone demethylases and participate in cardiac development. Jumonji domain containing 5 (JMJD5) is responsible for the embryonic development through removing methyl moieties from H3K36me2 histone, and has proproliferative effect on heart and eye development. However, the protective role of JMJD5 against oxygen-glucose deprivation and reperfusion (OGD/R)-induced injury in cardiomyocytes has not been fully understood. Firstly, myocardial ischemia/reperfusion (I/R) rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…The present study verified that autophagic flux and mitophagy were inhibited or reduced in both ischaemic and pressure‐overload HF mice, and involved in LC3II, PINK1, PRKN and BECN1 related pathways, although discrepancies existed in the degree and nature of the pathway depending on the HF model, which was generally consistent with the results of the previous studies (Kubli & Gustafsson, 2012; Liu et al., 2012; Morales et al., 2020; Nah et al., 2022; Wang et al., 2018). In addition, HIF1α in the myocardium of mice with both aetiologies of HF was also significantly reduced in the present study, which was consistent with the decreased HIF1α in the study of oxygen–glucose deprivation and reperfusion‐induced injury in cardiomyocytes (Zhang et al., 2022). Combined with the current evidence, it can be concluded that poor mitophagy may serve as a ‘hallmark’ of chronic HF and is closely linked to its pathological development.…”
Section: Discussionsupporting
confidence: 91%
“…The present study verified that autophagic flux and mitophagy were inhibited or reduced in both ischaemic and pressure‐overload HF mice, and involved in LC3II, PINK1, PRKN and BECN1 related pathways, although discrepancies existed in the degree and nature of the pathway depending on the HF model, which was generally consistent with the results of the previous studies (Kubli & Gustafsson, 2012; Liu et al., 2012; Morales et al., 2020; Nah et al., 2022; Wang et al., 2018). In addition, HIF1α in the myocardium of mice with both aetiologies of HF was also significantly reduced in the present study, which was consistent with the decreased HIF1α in the study of oxygen–glucose deprivation and reperfusion‐induced injury in cardiomyocytes (Zhang et al., 2022). Combined with the current evidence, it can be concluded that poor mitophagy may serve as a ‘hallmark’ of chronic HF and is closely linked to its pathological development.…”
Section: Discussionsupporting
confidence: 91%
“…The BCL2 family of proteins, comprising anti-apoptotic and pro-apoptotic members, influences BNIP3-mediated mitophagy [ 60 ]. BNIP3 contains a BH3 domain that enables its interaction with anti-apoptotic BCL2 family members, such as BCL2 and BCL-XL [ 61 ]. This interaction releases the pro-apoptotic protein Beclin-1, initiating autophagy.…”
Section: Discussionmentioning
confidence: 99%